The perspective of current and retired world class, elite and national athletes on the inclusion and eligibility of transgender athletes in elite sport - Shaw, A. L.; Williams, A. G.; Stebbings, G. K.; Chollier, M.; Harvey, A.; Heffernan, S. M. (Journal of Sports Sciences, 2024)
There has been limited empirical study allowing athletes to voice their opinions on transgender participation in elite sport. This study surveyed 175 national, elite and world class athletes eligible to compete in the female category regarding transgender inclusion and eligibility. The study compared current Olympic versus current Olympic Recognised sports, elite versus world class, and current versus retired Olympic sport athletes. Most athletes favoured biological sex categorisation (58%) and considered it unfair for trans women to compete in the female category, except for precision sports. This view was held most strongly by world class athletes regarding their own sport (77% unfair, 15% fair). For trans men inclusion in the male category, most athletes considered it fair, except for Olympic sport athletes regarding contact sports (49% unfair, 27% fair) and sports heavily reliant on physical capacity (53% unfair, 29% fair). Notwithstanding those views, athletes (81%) believed sporting bodies should improve inclusivity for transgender athletes. Opinion varied somewhat according to career stage, competitive level and sport type. Nevertheless, athletes in the present study favoured categorisation by biological sex and did not support trans women eligibility for the female category in sports reliant on performance-related biological factors that differ between sexes.